PSYCHOTIC DEPRESSION: A PECULIAR PRESENTATION FOR MULTIPLE SCLEROSIS - GÜNAL, DİLEK; AĞAN YILDIRIM, KADRİYE (TAYLOR & FRANCIS LTD, 2009)
Multiple sclerosis (MS) is frequently associated with a number of different psychiatric syndromes. Solely psychiatric syndrome may be the first clinical presentation of multiple sclerosis. We report a patient whose first attack was psychotic depression. The present case emphasizes that psychiatric symptoms can occur at any time during the course of the disease and, moreover, may be the presenting feature.
Keywords: attack; depression; imaging; interferon; multiple sclerosis; psychosis; SYMPTOMS; ONSET